Projeto cooesperança: uma experiência de capital social em Santa Maria - RS - Silva, Marco Aurélio da (2013)
The purpose of this research is to analyze the importance of Cooesperança Project regarding the performance of the Solidarity Economy for the development and maintenance of social capital in Santa Maria - RS . Justifies the choice of the theme by the proposed fair Soliária Economy and its national expression as an alternative to the current economic system . For the theoretical development of research, bring up the hypothesis that the practices of cooperatives , associative , participatory and community Cooesperança the design actions may be examples of social capital to the city of Santa Maria . For the development of this research , in the first part the author was based on theoretical principles defended by Robert Putnam and Alexis de Tocqueville . Already in a second step , the purpose was to analyze the results of 30 interviews with merchants Cooesperança Project participants and consumers in Santa Maria - RS , through the application of survey research in 2013 .